Analysis of Clean Water Needs and Wastewater Management of Japfa Office Building - Yuli Sulistiyohadi; Agus Jumkhairul; Era Agita Kabdiyono (Jurnal Teknik dan Science, 2025)
Japfa Compeed Building is an office building managed by PT Ometraco Arya Samanta, has 7 floors and has just started operating and was inaugurated in January 2025. The building is located at Jalan Daan Mogot KM 12 No. 9, Cengkareng, West Jakarta. The building covers an area of approximately 29,272 m2. To ensure employee comfort, an effective clean water and wastewater management system is required, complying with the latest Indonesian National Standard, SNI 8153:2015. To meet the clean water needs of a population of 662, 39.72 m3 of clean water is required per day. The ground water tank capacity is 13.24 m3, while the roof water tank capacity is 2.92 m3. This office building has a Wastewater Treatment Plant (WWTP) with a water discharge capacity of 40 m3/day. Some of the wastewater is treated through a Wastewater Treatment Plant (WWTP), with a maximum capacity of 10 m3/day of recycled water. The water discharge savings generated from the WWTP reach 101 m3 per month, according to daily water discharge checks. The building also utilizes a Water Level Control (WLC) system for the distribution of clean and recycled water, enabling automatic water level control.